Antibacterial Effectiveness Of Green Shell Nanocitosan (Perna Viridis) On The Growth Of The Bacteria Prevotella Intermedia (In Vitro Study) - Widyastuti, Noor Hafida; Cahyani, Cahyani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Green mussel shell nanochitosan is a size modification of chitosan obtained from green mussel shells that have been processed with specific standards. Nanochitosan from green mussel shells has not been researched for its anti-bacterial properties against Prevotella intermedia bacteriaPurpose: This study aims to determine the antibacterial effect on the growth of Prevotella intermedia bacteria. Method: This research is laboratory research using a posttest only control group design.Method: This research is laboratory research using a posttest only control group designResult: Nanochitosan with concentrations of 0.5%, 1%, 1.5% and 2% was able to inhibit the growth of Prevotella intermedia bacteria. The test results using the One Way ANOVA test obtained a value of p = 0.000 so that p < 0.5 and it was stated that there was a significant difference between treatment groups on the growth inhibition value of Prevotella intermedia bacteriaConclusion: There is an anti-bacterial effect and there is an inhibitory zone in the culture of Prevotella intermedia bacteria that has been incubated within 24 hours with 37°C. The greater the concentration used, the more effective the antibacterial agent is